2009
DOI: 10.1162/coli.08-012-r1-06-90
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Contextual Polarity: An Exploration of Features for Phrase-Level Sentiment Analysis

Abstract: Many approaches to automatic sentiment analysis begin with a large lexicon of words marked with their prior polarity (also called semantic orientation). However, the contextual polarity of the phrase in which a particular instance of a word appears may be quite different from the word's prior polarity. Positive words are used in phrases expressing negative sentiments, or vice versa. Also, quite often words that are positive or negative out of context are neutral in context, meaning they are not even being used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
365
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(387 citation statements)
references
References 31 publications
6
365
0
8
Order By: Relevance
“…A document contains multiple opinions. The task at phrase level is to determine the opinion that is being expressed by a phrase [28]. Aspect level performs fine-grained analysis.…”
Section: Related Workmentioning
confidence: 99%
“…A document contains multiple opinions. The task at phrase level is to determine the opinion that is being expressed by a phrase [28]. Aspect level performs fine-grained analysis.…”
Section: Related Workmentioning
confidence: 99%
“…However, some Unsupervised Learning techniques have been very successful as well, as it is unsupervised technique based on the PMI-IR algorithm that is used to estimate the semantic orientation of a phrase by measuring the similarity of pairs of words or phrases [60]. Alternative methods have been proposed, like the Bootstrapping Method for Building Subjectivity Lexicons for Languages with Scarce Resources [6], the techniques for generating a quality lexicon [59], the recognition of contextual polarity in [69] and the gradability of subjective sentences based on adjective orientation [26]. In all these cases, the focus of the research is at the sentence/phrase level.…”
Section: Through 2014mentioning
confidence: 99%
“…The context in which a term is used can change its meaning, which is particularly true for adjectives in sentiment lexicons [3]. Several evaluations have shown that sentiment detection methods should not neglect contextual information [4,5], and have identified context words with a high impact on the polarity of ambiguous terms [6]. Besides the ambiguity of human language, another bottleneck for sentiment detection methods is the time-consuming creation of sentiment dictionaries.…”
Section: Related Workmentioning
confidence: 99%